The Canada Packers Collection : selected oil paintings and works on paper - Finlay, Karen (Toronto : Art Gallery of Ontario, 1982)
Alfsen, John Martin ; Brooker, Bertram ; Carmichael, Franklin ; Carr, Emily ; Casson, A.J. ; Clark Paraskeva ; Cosgrove, Stanley ; Courtice, Rody Kenny ; Harris, Lawren ; Hewton, Randolf Stanley ; Hamphrey, Jack ; Jackson, A.Y. etc.
The Canada Packers Collection selected oil paintings and works on paper / La Collection de Canada Packers oeuvres à l'huile et sur papier, Art Gallery of Ontario, Toronto, Feb. 27 - Apr. 11, 1982
Text French-English
kunstcatalogus